Presentation: Citizenship, State and ethnicity in the Andean communities - Grández Moreno, Félix (1995)
In this issue of Allpanchis we have brought together a set of collaborations around the problem of citizenship of Andean populations and communities. This old problem has been receiving renewed attention in academic circles. It is no coincidence for them that the four works that we present are part of individual university theses. We are also witnessing an incipient social and political debate, driven basically by groups and institutions of civil society in a context in which citizenship seems to be the symbolic continent where the fight against social exclusion and the search for national integration take place.